Chemical composition of rhizome essential oil of Ginger Lily (Hedychium) from the Western Ghats, India (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Hedychium species are perennial rhizomatous herbs with high-quality terpenoids. In the present study, the essential oil yield and composition from dried rhizomes of Hedychium taxa collected from the Western Ghats of India were evaluated. Essential oils were obtained by hydro-distillation, and the yield varied from 0.4–3.96% (v/w). The components were identified by gas chromatography, flame ionisation detector, and gas chromatography-mass spectrometry. A total of 73 components were identified among the eight taxa, and a maximum of 90.20% (31 compounds) and a minimum of 66.41% (36 compounds) of the oil constituents were identified from Hedychium matthewii and Hedychium forrestii var. forrestii, respectively. β-linalool was the major constituent in the oils of Hedychium coronarium (17.72%), H. forrestii (25.38), H. flavescens (18.64%), and H. matthewii (48.41%). β-pinene was the major constituent in the oils of H. forrestii var. palaniense (18.31%) and H. flavum (20.17%), whereas 1,8-cineole was the dominant component in H. venustum (25.81%) and α-cadinol in H. spicatum (18.59). The results showed that geographic factors greatly influence the essential oil composition in Hedychium. Essential oil composition in H. coronarium and H. spicatum from the Western Ghats significantly differs from other geographical regions of origin. Hence, H. coronarium and H. spicatum from the Western Ghats are two chemotypes for rhizome essential oils.